Age and speciation of iodine in groundwater and mudstones of the Horonobe area, Hokkaido, Japan: Implications for the origin and migration of iodine during basin evolution. (15th October 2016) - Togo, Yoko S.; Takahashi, Yoshio; Amano, Yuki; Matsuzaki, Hiroyuki; Suzuki, Yohey; Terada, Yasuko; Muramatsu, Yasuyuki; Ito, Kazumasa; Iwatsuki, Teruki
Abstract: This paper reports the concentration, speciation and isotope ratio ( 129 I/ 127 I) of iodine from both groundwater and host rocks in the Horonobe area, northern Hokkaido, Japan, to clarify the origin and migration of iodine in sedimentary rocks. Cretaceous to Quaternary sedimentary rocks deposited nearly horizontally in Tenpoku Basin and in the Horonobe area were uplifted above sea level during active tectonics to form folds and faults in the Quaternary. Samples were collected from the Pliocene Koetoi and late Miocene Wakkanai formations (Fms), which include diatomaceous and siliceous mudstones. The iodine concentration in groundwater, up to 270 μmol/L, is significantly higher than that of seawater, with the iodine enrichment factor relative to seawater reaching 800–1500. The iodine concentration in the rocks decreases from the Koetoi to Wakkanai Fms, suggesting that iodine was released into the water from the rocks of deeper formations. The iodine concentration in the rocks is sufficiently high for forming iodine-rich groundwater as found in this area. X-ray absorption near edge structure (XANES) analysis shows that iodine exists as organic iodine and iodide (I − ) in host rocks, whereas it exists mainly as I − in groundwater. The isotope ratio is nearly constant for iodine in the groundwater, at [0.11–0.23] × 10 −12, and it is higher for iodine in rocks, at [0.29–1.1] × 10 −12, giving iodine ages of 42–60 Ma and 7–38 Ma, respectively. Some iodine in groundwater must have originated from Paleogene and even late Cretaceous Fms, which are also considered as possible sources of oil and gas, in view of the old iodine ages of the groundwater. The iodine ages of the rocks are older than the depositional ages, implying that the rocks adsorbed some iodine from groundwater, which was sourced from greater depths. The iodine concentration in groundwater decreases with decreasing chlorine concentration due to mixing of iodine-rich connate water and meteoric water. A likely scenario is that iodine-rich brine formed during the long-term basin evolution from the Cretaceous to Quaternary and that this brine was diluted by mixing with meteoric water during uplifting and denudation of the area.